(untitled) (Castilla. Estudios de Literatura, 2020)
Through a comparison between Japanese poetic forms and western poetry, this paper studies the way in which Octavio Paz managed to transcend these forms to create his own ‘Japanese poetry’ and what the uniqueness of that part of this poetic production consists of. For this, creative elements of Paz himself have been used, as well as his essay works and also the contribution of different authors whose competences in the field of literary theory allowed to develop the poetic language throughout the twentieth century.